Accounting and silence: The unspeakable, the unsaid, and the inaudible - Drujon d'Astros, Caecilia; Morales, Jérémy; Leca, Bernard (Contemporary Accounting Research, 2024)
Abstract This paper studies accounting and silence. Building on studies of accounting talk and introducing theories of “silencing,” we highlight the role of accounting silences in the production of engaging organizational conversations. Through a qualitative case study, we identify three forms of silence—the unspeakable, the unsaid, and the inaudible—and their links to accounting. Silences create motivations to engage in further accounting talk, but they also deny certain groups a voice in those conversations. An impression of participation, openness, and transparency emerges despite unequal access and the silencing of certain groups. Accounting itself can be silenced to avoid uncomfortable topics, potential problems, and anxiety‐inducing uncertainties. This silencing may serve to preserve a useful ignorance, avoid being in the know, and build alluring narratives and engaging conversations. Accounting silences sustain such conversations by protecting them from alternative voices, unsettling knowledge, and narratives that are incompatible with the organization's preferred story.